2016
DOI: 10.1002/slct.201600128
|View full text |Cite
|
Sign up to set email alerts
|

Enantiospecific Formal Synthesis of Inthomycin C

Abstract: An enantiospecific synthesis of Hatakeyama's intermediate enynol has been accomplished in both enantiomeric forms. As these intermediates can be converted to (3R)‐inthomycin C and (3S)‐inthomycin C through respective enynol intermediates using reported procedures, present effort may be regarded as formal synthesis of inthomycin C in both enantiomeric forms. Our synthesis highlights the use of pantolactone chiral pool and thus reconfirms the previously assigned absolute stereochemistry as 3R to the natural prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…To date, there have been four reported asymmetric total syntheses of inthomycin C by Taylor, Ryu, Hatakeyama and Hale . Additionally, a formal synthesis of racemic material has been reported by Maulide, and an asymmetric formal synthesis has been reported by Reddy . Recently, Hale and Hatakeyama jointly confirmed the absolute configuration of (−)-(3 R )-inthomycin C by collaboration .…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…To date, there have been four reported asymmetric total syntheses of inthomycin C by Taylor, Ryu, Hatakeyama and Hale . Additionally, a formal synthesis of racemic material has been reported by Maulide, and an asymmetric formal synthesis has been reported by Reddy . Recently, Hale and Hatakeyama jointly confirmed the absolute configuration of (−)-(3 R )-inthomycin C by collaboration .…”
mentioning
confidence: 91%
“…10 Additionally, a formal synthesis of racemic material has been reported by Maulide, 11 and an asymmetric formal synthesis has been reported by Reddy. 12 Recently, Hale and Hatakeyama jointly confirmed the absolute configuration of (−)-(3R)-inthomycin C by collaboration. 13 It is noteworthy that all published syntheses of (−)-(3R)-inthomycin C (ranging between 11−16 steps) rely on a Stille cross-coupling reaction to form the C7−C8 bond and differ in their approach toward the synthesis of the β-hydroxyl carbonyl moiety.…”
mentioning
confidence: 96%
“…Two years later, Reddy and co-workers accomplished enantiospecific formal syntheses of both inthomycins C ((+)- 3 ) and inthomycin C ((−)- 3 ) using Hatakeyama’s enynol intermediate 82b ( Scheme 15 ) [ 66 ]. The synthesis commenced with the benzylation of ( R )-pantolactone 108a to produce (+)- 109a in 85% yield.…”
Section: Rewiewmentioning
confidence: 99%
“…Hatakeyama groups demonstrated that inthomycin C ((-)-3) has (3R)-and not (3S)-stereochemistry [57]. Careful reappraisal of the previously published work [21,22,50,60] [66]. The synthesis commenced with the benzylation of (R)-pantolactone 108a to produce (+)-109a in 85% yield.…”
Section: Soon After a Subsequent Collaboration Between The Hale Andmentioning
confidence: 99%
“…As reported by Kulkarni, the sensing performances of PANI to ethanol vapour were significantly improved upon inclusion of small concentrations of silver (Ag) nanoparticles. However, the PANI/Ag nanocomposite sensor exhibited poor response and inferior reproducibility [9][10].…”
Section: Introductionmentioning
confidence: 99%